PENGARUH PENGGUNAAN TEKS PERMAINAN BAHASA TERHADAP PRESTASI MAHASISWA PADA MATA KULIAH MORFOLOGI - Kingkin Puput Kinanti; Dwi Ulfa Nurdahlia (Universitas Muhammadiyah Malang, 2018)
This research belongs to experimental research, focusing about the usage influence of language game text on students’ achievements in Morphology course. The discussion aims to explain and elaborate the usage influence of language game text on students’ achievements in Morphology course.Data penelitian kemudian diolah dengan menggunakan uji Mann Whitney. Hasil uji hipotesis Mann Whitney aspek prestasi mahasiswa pada mata kuliah morfologi kelas eksperimen dan kelas kontrol memiliki Zhitung -2,090 dengan signifikansi 0,037 < 0,05 sehingga dapat disimpulkan bahwa hipotesis alternatif yang menyatakan bahwa ada perbedaan yang signifikan pada prestasi mahasiswa pada matakuliah morfologi dengan pemberian teks permainan bahasa diterima.This research used a quantitative approach with the type of quasi-experimental research. Control Group Pre Test – Post Test Design was a selected research design for this experimental research. The population is students of 2016 class in odd semester of academic year 2017/2018. The samples used in this research were 36 students of 2016 class in IKIP Budi Utomo academic year 2017/2018. The phases of quasi-experiments design describes as follows, (1) identifying the characteristics of the research subjects, (2) giving pre-test (pretesting) to the experimental class and the control class, (3) giving treatment in the form of language game text to the experiment class and conventional text to the control class, (4) giving post-test to the experimental class and the control class. The data obtained from the research then was analyzed by using Mann Whitney test. The result of Mann Whitney hypothesis test of students’ achievements aspect in Morphology course between experiment and control classes had Zcount -2.090 with the significance of 0.037 <0.05 therefore it can be concluded that the alternative hypothesis stated that there is significant difference on students’ achievements in Morphology course by giving language game text is conformed to be accepted.